IMPROVING TEACHER DISCIPLINE IN TEACHING ATTENDANCE IMPLEMENTING THE REWARD AND PUNISHMENT SYSTEM IN SCHOOLS - Intan Afriaty (CV Naskah Aceh, 2024)
This research is School Action Research which aims to determine the improvement of teachers' attendance discipline in teaching through the reward and punishment system at SMP Negeri 1 Satu Atap Sungai Mandau. The subjects of this study were 7 teachers of SMP Negeri 1 Satu Atap Sungai Mandau. This research was conducted in the even semester of the 2020/2021 academic year. The results showed that the reward and punishment system can improve teachers' attendance in teaching. The implementation of pre-cycle learning at the first meeting showed that all teachers were present on time because it was the first day of school for the 2020/2021 school year.The implementation of learning in the first cycle showed that 5 teachers were late to teach in the class, and after the implementation of learning in the second cycle the teacher's discipline in teaching reached 85% based on the responses of respondents (teachers) regarding the application of the reward and punishment system, while based on observations 74% of teachers were still less than 5 minutes late because the location was difficult to reach.